The effects of ankle Kinesio® taping on ankle stiffness and dynamic balance - Fayson, S. D.; Needle, A. R.; Kaminski, T. W. (Research in Sports Medicine, 2013)
The purpose of this study was to determine the effects of Kinesio® taping on static restraint and dynamic postural control of the ankle joint. Thirty female subjects with no history of ankle injury participated in this study. Subjects were tested for passive ankle laxity and stiffness, and time to stabilization following forward, backward, medial, and lateral hops. Subjects were tested prior to tape application, immediately following application, and following 24 hours of use. Differences between taping conditions were investigated using analyses of variance and pairwise comparisons. Stiffness increased following initial application and 24 hours of Kinesio® tape use (F = 6.99, p = .003), despite no observed changes in ankle laxity (F = 0.77, p = .49); however, no changes were observed in time-to-stabilization (F = 0.03, p = .97). Our results suggest that Kinesio® tape may improve static restraint in the ankle joint without altering peak motion or dynamic postural control. A future investigation into Kinesio® tape efficacy in injury prevention or rehabilitation is warranted.